Investigation of Natural Radioactivity in a Monazite Processing Plant in Japan. Issue 3 (September 2017) - Iwaoka, Kazuki; Yajima, Kazuaki; Suzuki, Toshikazu; Yonehara, Hidenori; Hosoda, Masahiro; Tokonami, Shinji; Kanda, Reiko
Abstract : Abstract: Monazite is a naturally occurring radioactive material that is processed for use in a variety of domestic applications. At present, there is little information available on potential radiation doses experienced by people working with monazite. The ambient dose rate and activity concentration of natural radionuclides in raw materials, products, and dust in work sites as well as the 222 Rn and 220 Rn concentrations in work sites were measured in a monazite processing plant in Japan. Dose estimations for plant workers were also conducted. The activity concentration of the 238 U series in raw materials and products for the monazite processing plant was found to be higher than the relevant values described in the International Atomic Energy Agency Safety Standards. The ambient dose rates in the raw material yard were higher than those in other work sites. Moreover, the activity concentrations of dust in the milling site were higher than those in other work sites. The 222 Rn concentrations in all work sites were almost the same as those in regular indoor environments in Japan. The 220 Rn concentrations in all work sites were much higher than those in regular indoor environments in Japan. The maximum value of the effective dose for workers was 0.62 mSv y −1, which is lower than the reference level range (1–20 mSv y −1 ) for abnormally high levels of natural background radiation published in the International Commission of Radiological Protection Publication 103.